The kaiser's web [compact disc, unabridged] - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2021)
Two candidates are vying to become Chancellor of Germany. One is a patriot having served for the past sixteen years, the other a usurper, stoking the flames of nationalistic hate. Both harbor secrets, but only one knows the truth about the other. They are on a collision course, all turning on the events of one fateful day - April 30, 1945 - and what happened deep beneath Berlin in the Fürherbunker. Did Adolph Hitler and Eva Braun die there? Did Martin Bormann, Hitler's close confidant, manage to escape? And, even more important, where did billions in Nazi wealth disappear to in the waning days of World War II? The answers to these questions will determine who becomes the next Chancellor of Germany. From the mysterious Chilean lake district, to the dangerous mesas of South Africa, and finally into the secret vaults of Switzerland, former-Justice Department agent Cotton Malone discovers the truth about the fates of Hitler, Braun, and Bormann. Revelations that could not only transform Europe, but finally expose a mystery known as the Kaiser's web.